Analysis of the Effect of Renal Replacement Therapy: In the Prolonged Extracorporeal Membrane Oxygenation Patients - Park, Hyun-Seok (The Korean Society for Thoracic and Cardiovascular Surgery, 2014)
BACKGROUND: This paper aimed to verify the effects of renal replacement therapy on changing the levels of serum creatinine for different veno-arterial and veno-venous configurations in prolonged extracorporeal membrane oxygenation (ECMO) patients. METHODS: The subjects were chosen 71 patients who had undergone more than 1,440 minutes (24 hours) of the therapy from among 117 patients who had undergone ECMO insertion between January 2008 and December 2012. The patients were separated into the veno-arterial configuration group I (51 patients) and the veno-venous configuration group II (20 patients). The difference in the level of serum creatinine (ΔCr) between before or just after ECMO insertion (Cr(I)) and the level when the pump time was between 2,880 and 4,320 minutes (Cr(F)) was checked (ΔCr=Cr(F)−Cr(I)), and the average ΔCr for each group was compared using a Student t-test at the confidence interval (CI) of 95%. RESULTS: The change in the level of serum creatinine was an increase of 0.341 mg/dL (σ=0.9202) for group I and a decrease of 0.120 mg/dL (σ=1.5292) for group II. The change was significantly high for group I (p=0.011, CI=95%). Meanwhile, within group I, when renal replacement therapy was not done, there was a significant increase in the level of serum creatinine (p=0.009, CI=95%). CONCLUSION: For ECMO insertion patients whose pump time was more than 1,440 minutes, there was a significant change in the level of serum creatinine when renal replacement therapy was not done, for the veno-arterial configuration of group I.